Genetic diversity and population structure of Pyrus regelii in South Kazakhstan based on ISSR markers - GULNARA T. SITPAYEVA; AINAGUL ABDUKHADYR; ALEXANDR I. SHMAKOV; NIKOLAI E. ZVEREV; ANASTASIA M. KOLTUNOVA; AINUR S. YESZHANOVA; LAURA SH. SHADMANOVA; BEKTEMIR B. OSMONALI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sitpayeva GT, Abdukhadyr A, Shmakov AI, Zverev NE, Koltunova AM, Yeszhanova AS, Shadmanova SH, Osmonali BB. 2025. Genetic diversity and population structure of Pyrus regelii in South Kazakhstan based on ISSR Markers. Biodiversitas 26: 4714-4729. Pyrus regelii is a relic wild pear species with a restricted distribution in the mountainous regions of South Kazakhstan. Despite its ecological and breeding importance, its genetic structure has never been systematically studied. This study provides the first comprehensive assessment of the genetic and morphological diversity of 5 natural populations from the Karatau and Kyrgyz Alatau ranges. A total of 12 ISSR primers were screened, with 6 highly polymorphic primers selected; these generated 113 loci, of which 112 were polymorphic (98.9%). The number of alleles per locus ranged from 3 to 7 (mean Na = 1.78 per locus). Expected Heterozygosity (He) varied between 0.24-0.31, while Observed Heterozygosity (Ho) was consistently lower, indicating slight inbreeding. Shannon's information index ranged from 0.36-0.47. Pairwise Fst values reached 0.3451 between populations from different mountain systems, reflecting strong differentiation and limited gene flow across orographic barriers. STRUCTURE analysis (K = 3) and PCA confirmed three major genetic clusters, with signs of admixture in several populations. Morphological assessment showed variation in plant height (0.2-3.5 m), crown diameter (0.1-4.4 m), and leaf forms. Heterophyllous populations occurred only in the Kyrgyz Alatau, while Karatau populations were uniform with dissected leaves. The combined genetic and phenotypic evidence indicates adaptive variation that helps survival in arid and cold environments. However, fragmented distribution and isolation make the species vulnerable. Populations with unique alleles (Almalysay) and genetically isolated groups (Bozturgai, Berkara) should be prioritized for in situ conservation and monitoring. Ex situ measures, including seed banks and living collections, are necessary to capture the full spectrum of genetic diversity. Beyond conservation, the adaptive traits of P. regelii offer valuable genetic resources for breeding climate-resilient pear cultivars. Overall, this study establishes the first molecular baseline for P. regelii in Kazakhstan and offers a scientific basis for integrated strategies in conservation and sustainable utilization.